PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN SEPEDA MOTOR HONDA SCOOPY (Survei Konsumen Pada PT.Capella Dinamik Nusantara Duri) - Nilam Ayu Lestari; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine the effect of Brand Image and Product Quality on consumer purchase intention of motorcyle honda Scoopy (Consumer Survey At PT.Capella Dinamika Nusantara Duri). The Brand Image as a variabel (X1), Product Quality as variabel (X2) and Consumer purchase intention as variabel (Y). This research was conducted at PT.Capella Dinamik Nusantara Duri, and took the number of respondents is 100 people. The data from the questiommaire id further processed using statitical analysis that is simple linier analysis, multiple linier analysis, determination analysis, and significance test with t test (partial), F (simultaneous) test. The results showed that the test results of the first test hypotesis that is brand image to consumer purchase intention is tcount (8,992) > t table (1,984) means brand image significant effect on consumer purchase intention. Both product quality of consumer purchase intention is tcount (8,798) > t table (1,984) meaning there is significant influence between product quality to consumer purcahse intention. F test result of brand image and product quality of consumer purchase intention are F arithmetic (73,464) > F table (3,090). This means that the brand image ad product quality simultaneously significantly influence consumer buying intention.Keywords : Brand Image, Product Quality, Consumer Purchase Intention.